De-escalated radiotherapy for HER2-overexpressing breast cancer patients with 1-3 positive lymph nodes undergoing anti-HER2 targeted therapy - Liu, Jing; Huang, Suning; Bi, Zhuofei; Zhang, Xiaoxue; He, Ziqing; Lan, Xiaowen; Tan, Yuting; Lin, Xiao; Zhou, Wenyi; Huang, Xiaobo (Frontiers in Oncology, 2023)
Abstract Background: In the era of anti-HER2 targeted therapy, the potential clinical feasibility of considering HER2-overexpressing breast cancer cases presenting with 1 3 positive axillary lymph nodes as low-risk, and thereby contemplating postoperative radiotherapy reduction, remains an important subject for in-depth examination. The aim of this retrospective study was to evaluate the effectiveness of de-escalated radiotherapy in T1-2N1M0 HER2-overexpressing breast cancer patients receiving anti-HER2 targeted therapy. Specifically, omitting regional lymph node irradiation (RNI) after breast-conserving surgery and only performing whole-breast irradiation or omitting postmastectomy radiation therapy. Methods: A retrospective analysis was conducted on 429 patients with stage T1 2N1M0 primary invasive HER2-overexpressing breast cancer from our center between 2004 and 2018. Patients who received anti-HER2 targeted therapy were divided into an RNI group and a no RNI group to assess the role of RNI. The prognostic role of RNI was investigated via the Kaplan-Meier method and Cox proportional hazards modeling. Results: The median follow-up time was 46.8 months (range 7.1–225.8 months). In the anti-HER2 targeted therapy group RNI yielded no significant improvements in invasive disease-free survival (IDFS) (p = 0.940), local-regional recurrence-free survival (p = 0.380), distant metastases-free survival (p = 0.698), or overall survival (p = 0.403). Estrogen receptor (ER) status (hazard ratio [HR] 0.105, 95% confidence interval [CI] 0.023–0.749, p = 0.004) and lymph vascular invasion status (LVI) (HR 5.721, 95% CI 1.586–20.633, p = 0.008) were identified as independent prognostic factors for IDFS, and ER-positive and LVI-negative patients exhibited better prognoses. Conclusions: Omitting RNI may be a safe option in T1-2N1 HER2-overexpressing breast cancer patients receiving standardized anti-HER2 targeted therapy; particularly in ER-positive or LVI-negative subgroups.